Gender associated muscle-tendon adaptations to resistance training - McMahon, G.; Morse, C. I.; Winwood, K.; Burden, A.; Onambele, G. L. (PLOS ONE, 2018)
Purpose: To compare the relative changes in muscle-tendon complex (MTC) properties following high load resistance training (RT) in young males and females, and determine any link with circulating TGFß-1 and IGF-I levels.